HUBUNGAN KEPATUHAN MINUM OBAT DENGAN GULA DARAH PASIEN DM TIPE II DI PUSKESMAS TAMALANREA MAKASSAR: HUBUNGAN KEPATUHAN MINUM OBAT DENGAN GULA DARAH PASIEN DM TIPE II DI PUSKESMAS TAMALANREA MAKASSAR - Asmaul Husna Husna; Nurhaedar Jafar; Healthy Hidayanty; Djunaidi M.Dachlan; Abdul Salam (Jurnal Gizi Masyarakat Indonesia (The Journal of Indonesian Community Nutrition), 2022)
Introduction: Diabetes mellitus is a metabolic disease characterized by high blood sugar levels (hyperglycemia), so the blood sugar levels of DM patients need to be controlled. One way of controlling DM is to take medication, but there are still many patients who are not compliant during treatment so that blood sugar becomes uncontrolled. Objective: To determine the correlation between medication compliance and blood glucose in Type II DM patients in the Tamalanrea Public Health Center working area. Methods: This study used a cross-sectional design. The sample is 85 patients with Type II DM in the working area of ​​the Tamalanrea Health Center which were selected by simple random sampling. The instruments used in the study were MMAS-8 to measure compliance with medication consumption and the Easy Touch GCU tool to measure blood glucose. Results: The results showed that most of the patients had a low level of medication compliance (61.2%). The majority had uncontrolled blood sugar (77.6%). The results of the chi-square test showed a p-value of 0.000 (<0.05). Conclusion: There was a correlation between medication compliance and blood glucose in Type II DM patients in the working area of ​​the Tamalanrea Health Center. Keywords: Compliance, Diabetes Mellitus, Blood Glucose